2012
DOI: 10.1086/667611
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-Level Gas Exchange and Foliar Chemistry of Common Old-Field Species Responding to Warming and Precipitation Treatments

Abstract: We investigated the shifts in plant carbon (C) and water dynamics by measuring rates of photosynthesis, transpiration, and instantaneous water use efficiency (WUE) in three common species of ''old-field'' plants-two C 3 forb species (Plantago lanceolata and Taraxacum officinale) and one C 3 grass species (Elymus repens)-under 12 experimentally altered temperature and precipitation regimes at the Boston Area Climate Experiment (BACE) in Waltham, Massachusetts. We also measured shifts in foliar C and nitrogen (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The increases in NPP may be attributed to prolonged growing seasons with earlier beginnings and later endings under continuous warming (Wan et al ., ), increased soil nutrient mineralization and plant nutrient uptake (Rustad et al ., ; Sardans et al ., ), and also stimulated photosynthetic rates at higher temperatures (Rustad et al ., ; Luo et al ., ; Wu et al ., ). However, stimulated photosynthesis may be a minor cause of the increase in NPP since warming had no significant effect on photosynthesis according to previous studies (Stirling et al ., ; Zhou et al ., ; Rogers et al ., ). The non‐significant warming effect on ANPP probably resulted from the translocation of photosynthates from aboveground biomass to roots under warming, which was evidenced by the increased BNPP as well as f BNPP under warming (all P < 0.05, Table ; Figs b, d and a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The increases in NPP may be attributed to prolonged growing seasons with earlier beginnings and later endings under continuous warming (Wan et al ., ), increased soil nutrient mineralization and plant nutrient uptake (Rustad et al ., ; Sardans et al ., ), and also stimulated photosynthetic rates at higher temperatures (Rustad et al ., ; Luo et al ., ; Wu et al ., ). However, stimulated photosynthesis may be a minor cause of the increase in NPP since warming had no significant effect on photosynthesis according to previous studies (Stirling et al ., ; Zhou et al ., ; Rogers et al ., ). The non‐significant warming effect on ANPP probably resulted from the translocation of photosynthates from aboveground biomass to roots under warming, which was evidenced by the increased BNPP as well as f BNPP under warming (all P < 0.05, Table ; Figs b, d and a, b).…”
Section: Discussionmentioning
confidence: 99%
“…If photosynthetic carbon gain responds differently to these environmental changes than nitrogen uptake or allocation, leaf tissue chemistry could change. Interestingly, previous studies have found that warming can either increase ( Nijs et al 1996 ; Oleksyn et al 2003 ; Rodgers et al 2012 ) or decrease ( Yin 1993 ; Dormann and Woodin 2002 ; Reich and Oleksyn 2004 ; Suseela et al 2015 ) a plant species’ foliar nitrogen concentration. Altered foliar carbon and nitrogen concentrations can affect ecosystem-scale processes by influencing rates of photosynthesis, herbivore forage quality, plant litter chemistry and ultimately carbon and nutrient pathways ( Shaver et al 2001 ; Aerts et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that drought treatment significantly reduced E and g s of plants than wet treatment in greenhouses (Miyashita et al 2005, Miao et al 2015. Nevertheless, Rodgers et al (2012) found that a 50% increased rainfall treatment did not cause a significant shift in E of P. lanceolata compared to a 50% reduced rainfall treatment.…”
Section: Discussionmentioning
confidence: 72%